VERMICOMPOSTING OF INVASIVE SPECIES AZOLLA PINNATA WITH EISENIA FETIDA - Ramadevi,sunitha, (The Bioscan, 2022)
Earthworm species Eisenia foetida might be used in vermicomposting to turn the invasive weed Azolla pinnata into a resource in the water bodies of Kashmir Valley, India. The conversion rate for the first, second, third, and fourth fortnights was 17.91 ± 0.30%, 43.46 ± 0.67%, 83.15 ± 0.53%, and 100% correspondingly. Both the number of earthworms and biomass (g) rose by 68.66 ± 1.45 and 10.75 ± 0.47, respectively. There was a substantial association (p<0.05) between the beginning, final, and vermicomposting day counts of earthworms and the percent conversion rate. Organic nitrogen (0.84 ± 0.01 to 1.23 ± 0.09), total phosphorous (510 ± 2.9 to 661 ± 7.8), calcium (2040 ± 12 to 2500 ± 30), magnesium (564 ± 67 to 787 ± 20), sodium (20.30 ± 0.21 to 33.12 ± 0.51), and potassium (25.43 ±) were all found to be increasing in the vermicast. with the exception of total organic carbon, which showed a declining trend (41.43 ± 0.09 to 23.90 ± 0.35), every two weeks, from 1.40 to 40.30 ± 1.60.